The Natural Ambiguity of Native Species - Foster, Jennifer (UnderCurrents: Journal of Critical Environmental Studies, 2004)
Mainstream ecological wisdom suggests that native species are essential to the preservation and promotion of ecological health or integrity: they are often deemed to be the ‘natural’, ‘authentic’ and ‘original’ occupants of particular habitats. Philosophically and pragmatically, they are generally considered crucial to biodiversity at scales ranging from the local to global. The past five years in particular have witnessed an explosion of publications and workshops expounding the virtues of native species as the rightful residents of bioregionally defined locales, to the extent that commercial chain nurseries have even caught on and showcase native species from their stock.